2015
DOI: 10.3855/jidc.6492
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of quorum sensing and virulence factors in Pseudomonas aeruginosa isolates in Egypt

Abstract: Introduction: Pseudomonas aeruginosa is one of the most virulent nosocomial pathogens worldwide. Quorum sensing (QS) regulates the production of pathogenic virulence factors and biofilm formation in P. aeruginosa. The four genes lasR, lasI, rhlR,and rhlI were found to regulate this QS system. In this study, we aimed to assess the correlation between these four genes and QS-dependent virulence factors and to detect the inhibitory effect of clove oil on QS. Methodology: Fifty P. aeruginosa clinical isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
(51 reference statements)
3
17
1
Order By: Relevance
“…aeruginosa is coordinated by the las and rhl systems that function hierarchically for bacterial survival in the face of environmental changes, biofilm formation and control of several other virulence factors [ 10 , 12 ]. Although a decrease in the ability to express virulence factors has been reported due to the absence and/or mutations in genes related to such QS, this does not necessarily compromise the ability to cause infection due to regulation mediated by the rhl system [ 12 , 68 , 69 ] Our results are in agreement with a study carried out by Senturk et al [ 12 ] and Ruiz-Roldán et al [ 56 ]; however, disagreeing with Aboushleib et al [ 69 ], who reported gene deficiency in more than 60% in clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa is coordinated by the las and rhl systems that function hierarchically for bacterial survival in the face of environmental changes, biofilm formation and control of several other virulence factors [ 10 , 12 ]. Although a decrease in the ability to express virulence factors has been reported due to the absence and/or mutations in genes related to such QS, this does not necessarily compromise the ability to cause infection due to regulation mediated by the rhl system [ 12 , 68 , 69 ] Our results are in agreement with a study carried out by Senturk et al [ 12 ] and Ruiz-Roldán et al [ 56 ]; however, disagreeing with Aboushleib et al [ 69 ], who reported gene deficiency in more than 60% in clinical isolates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gram-negative Pseudomonas aeruginosa produces virulence factors, such as pyocyanin, elastase, lectin, and exotoxin A [47,48], and Gram-positive Staphylococcus aureus produces virulence factors such as fibronectin binding protein, hemolysin, protein A, lipase, and enterotoxin [49,50]. Studies have shown that the production of these virulence factors is regulated by the bacterial QS signaling systems [51,52]. Disruption of QS to control the production of virulence factors seems to be an attractive broad-spectrum therapeutic strategy.…”
Section: Biofilm Formation and Virulence Factorsmentioning
confidence: 99%
“…Certainly, pyocyanin secretion is under the control of the rhl systems. As well, PQS controls rhl-dependent virulence-factor production such as pyocyanin [ 34 ] , as regards lasR , the study done by Abou shleib and his colleagues found that there was no statistical significant value between pyocyanin production and the studied lasR gene [ 35 ]. In contrast, in our study we found a statistically significant difference between lasR -positive isolates and lasR -negative isolates regarding pyocyanin production ( P value=0.035).…”
Section: Discussionmentioning
confidence: 99%